PTU-254 What do general practitioners want from gastroenterology services in secondary care, and what are they happy managing in primary care?. (28th May 2012) - Basuroy, R; Ramage, J; Reynolds, M
Abstract : Introduction: Recent changes in the NHS have focussed on moving more services into primary care. General Practitioners (GPs) are rarely consulted over planning of secondary care services, nor are they asked on their own comfort in managing gastroenterological conditions. The results of a GP survey of confidence and service development are presented. Methods: An online survey (created on Google Docs) was emailed to 102 GP practices. GPs were asked to rate their confidence in managing gastroenterological conditions as well as rate service developments using a 5-point Likert scale (1—very low, 5—very high). Free text boxes allowed GPs to provide additional comments for qualitative analysis. Responses (n=52) within 28 days were analysed in Microsoft Excel. Results: Abstract PTU-254 table 1 outlines GPs' confidence in managing gastroenterological conditions while Abstract PTU-254 table 2 outlines their rating of service developments in chronic disease management, referral pathways and other services. GPs commented on the need for " clear referral pathways " and " rapid access clinics " outside of the 2-Week Rule remit. They wanted " clear plans " for shared care with " rapid access if problems " as well as " support from nurse specialists " and " access to telephone advice " for both patients and themselves. GPs wanted " workload implications to be recognised " and " money to follow the patient " if more patients are managed in primary care. Conclusion: The survey has identified which conditions GPs are confident managing in primary care and those which need additional support from secondary care. Future service development is needed in areas of chronic disease management, referrals pathways and allied services. GPs value rapid access to secondary care as well as patient access to SOS appointments and nurse specialists. Developing local pathways, such as with Map of Medicine, can help with referrals and managing chronic conditions in primary care. Online surveys are an easy way to ask GPs about their own confidence in managing gastroenterological conditions as well as their opinion on service developments. Competing interests: None declared.